Assessing variation in the effectiveness of IUCN protected area categorisation. What remotely sensed forest integrity and human modification reveals across the major tropical forest biomes. (October 2022) - Hirons, Samuel; Matilda Collins, C.; Singh, Minerva
Highlights: We focused on evaluating the efficacy of forested protected areas (PAs) across the three main tropical biomes- Congo Basin, Tropical Andes, insular Malaysia and Indonesia. PA efficacy was evaluated on the basis of ecoregional representation, human modification and forest integrity. Representation of key ecoregions varied with 7%, 11% and 22% of named ecoregions being unprotected within each major region. IUCN management categories play a minor role in influencing PA efficacy. PA size was an important determinant of PA efficacy. Abstract: One of the major threats facing protected areas (PAs) in hyper-diverse tropical forest ecosystems is human modification of their natural habitats. With a focus on forested PAs situated across three of the world's major tropical regions, the Congo Basin, insular Indonesia Malaysia and the Tropical Andes. We analyse their representation of identified ecoregions and remote sensing data of human modification and forest integrity levels within PAs and used a generalized linear modelling approach to estimate the influences on these pressures, with a particular focus on IUCN management categorisation, PA size, and geographic location. Representation of key ecoregions varied with 7%, 11% and 22% of named ecoregions being unprotected within each major region. Overall, the IUCN management category allocation played a minor role in influencing the modification and forest integrity observed within PAs. Instead, PA size was the most important determinant of these variables across the different regions under consideration. This work provides further evidence to suggest that the assignment of PAs to IUCN categories in their current form is not interpreted consistently across different regions and does not correspond to the conservation benefits expected to be conferred by this categorisation.